STRATEGIC TRANSFORMATION OF COMPENSATION SYSTEMS IN INDONESIA AFTER THE JOB CREATION LAW: A LITERATURE REVIEW - Putri Handayani; Agus Usman (ZILLZELL MEDIA PRIMA, 2026)
The compensation system in Indonesia is undergoing a paradigmatic transformation in line with the enactment of Law Number 11 of 2020 concerning Job Creation. The shift in philosophy from the dominant protective approach in Law Number 13 of 2003 to a paradigm based on flexibility and productivity opens up strategic space for organizations to redesign their compensation architecture. This study aims to analyze how the three pillars of modern compensation traditional bases for pay, incentive pay, and person-focused pay can be coherently integrated within the new regulatory framework. The research uses a qualitative approach with the type of library research. The data sources consist of Indonesian regulatory documents as primary data and textbooks and international scientific journals as secondary data, which are analyzed using thematic content analysis techniques. The validity of the data is ensured through source triangulation and methodological triangulation. The results of the analysis show that the three pillars are complementary and not substitutive. Traditional bases for pay serve as the foundation of internal justice and regulatory compliance, incentive pay acts as a strategic alignment mechanism between individual contributions and organizational goals, while person-focused pay is a long-term human capital investment instrument. The integration of the three requires a balance between internal consistency and market competitiveness formalized in Company Regulations or Collective Labor Agreements. The practical implications of this study confirm that sustainable competitive advantage in the post-Job Creation Law era can only be achieved through a compensation system that is at the same time legal, fair, competitive, and socially legitimized.